A Review of Acquisitions 1955-1962 of Western Asiatic Antiquities (II) - Barnett, Richard David
Asia Minor, Anatolia, Syria, Phoenicia, Palestine, South Arabia, the Mandaeans; zwei ugaritische Tontafeln L 84 und I, 85; vgl. p. 81.